2002
DOI: 10.2108/zsj.19.309
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor is Required for Prevention of Blood Clotting and for the Development of Vasculature and Bone in the Embryos of Medaka Fish, Oryzias latipes

Abstract: The aryl hydrocarbon receptor (AHR) is a member of ligand-activated transcription factors and conserved among vertebrates. To investigate the role of AHR in fish development, medaka embryos were treated with agonist (2,3,7,8-tetrachlorodibenzo-p-dioxin), antagonists (alpha-naphthoflavone and resveratrol), and inhibitor (piperonyl butoxide) of cytochromes (Cyts) P450 encoded by a battery of target genes. These embryos were found to have similar abnormal phenotypes. Among the most consistent phenotypes were bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Second, the early expression of AhR and ARNT in myocardial chicken embryo suggests that myocardial AhR and ARNT protein expressions may be involved in cardiac signaling during cardiogenesis (Chien et al, 1993;Walker et al, 1997). This was recently supported by several studies that showed that AhR-null mice develop cardiac hypertrophy, ventricular wall thickness, coronary artery hyperplasia, aortic hypertension, elevation of mean arterial pressure, and associated with decreased cardiac output as compared to AhR WT mice (Kawamura and Yamashita, 2002;Lund et al, 2003;Thackaberry et al, 2002;Vasquez et al, 2003).…”
Section: Physiological Roles Of Ahr and Its Regulated Genes In The Cvsmentioning
confidence: 91%
See 3 more Smart Citations
“…Second, the early expression of AhR and ARNT in myocardial chicken embryo suggests that myocardial AhR and ARNT protein expressions may be involved in cardiac signaling during cardiogenesis (Chien et al, 1993;Walker et al, 1997). This was recently supported by several studies that showed that AhR-null mice develop cardiac hypertrophy, ventricular wall thickness, coronary artery hyperplasia, aortic hypertension, elevation of mean arterial pressure, and associated with decreased cardiac output as compared to AhR WT mice (Kawamura and Yamashita, 2002;Lund et al, 2003;Thackaberry et al, 2002;Vasquez et al, 2003).…”
Section: Physiological Roles Of Ahr and Its Regulated Genes In The Cvsmentioning
confidence: 91%
“…Furthermore, studies on medaka fish embryos showed that exposure to TCDD induced vascular damage manifested by vascular hemorrhage and circulation failure. In that study, the TCDD-induced vascular damage was transiently suppressed by treatment with AhR antagonist, aNF, or CYP inhibitor, piperonyl butoxide (PBO), providing convincing evidence of AhR-and CYP-mediated mechanism (Kawamura and Yamashita, 2002) Chronic administration of TCDD or PCB (100 ng/kg/day) for 2 years to SpragueDawley rats was associated with an increased incidence of spontaneous cardiomyopathy (Jokinen et al, 2003). In addition, rats treated acutely with high concentrations of TCDD exhibited cardiac lesions and increased the atrial responsiveness to (-)-isoproterenol, a drug that increases heart rate and heart muscle contractions (Buu-Hoi et al, 1972;Hermansky et al, 1988;Kelling et al, 1987).…”
Section: Pathophysiological Roles Of Ahr and Its Regulated Genes In Tmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, studies on TCDD exposure to medaka fish embryos showed that TCDD induced vascular hemorrhage and blood clotting. However, the vascular damage could be suppressed by AhR antagonist or CYP inhibitor, further underscoring the role of AhR and CYPs in cardiovascular diseases (Kawamura and Yamashita, 2002). Although there are many studies which have examined the effects of AhR ligands, particularly TCDD, on the cardiovascular system, the mechanisms underlying the cardiotoxic effect of TCDD has not yet been explained definitively.…”
Section: Discussionmentioning
confidence: 99%